Word Construction Muhsin in the Qur'an as the Embodiment of the Character of a Complete Human Being - Suriyadi, Suriyadi; Usman, Usman; Jalwis, Jalwis (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
This article aims to construct the realization of the character of the plenary person in the Qur'an through the meaning of the word muhsin. The Qur'an has described the character of muhsin as a doer of good. The doer of good (muhsin) is the highest level of character according to the Quran, or the most ideal character. This article is conducted with thematic method as well as content analysis with the theory of the level of the plenary person in Sufism Abdul Karim al-Jilli namely bidayah, tawasut and khitam. This study found that the perpetrators of goodness (muhsin) according to the Qur'an are people who do all their obligations as well as possible, repay every badness with goodness and repay goodness with greater goodness, able to restrain their anger, forgive, always ask Allah's forgiveness for their sins and transgressions. This level is manifested in first, Ihsan deeds at the Al-Bidayah level (the initial level), namely the character of totality in doing good, and the character of forgiveness; second, the Al-Tawassuth level (the middle level) in the character of social empathy and emotional regulation; third, the Al-Khitam level (the last level) in the character of positive response, piety and tawadhu'. Artikel ini bertujuan untuk mengkonstruksi perwujudan karakter insan paripurna di dalam Al-Qur’an melalui makna kata muhsin. Al-Qur’an telah menggambarkan karakter muhsin sebagai pelaku kebaikan. Pelaku kebaikan (muhsin) adalah tingkatan karakter tertinggi menurut Al-Quran, atau karakter yang paling ideal. Artikel ini dilakukan dengan metode tematik sekaligus analisis isi (Content Analysis) dengan teori tingkatan insan paripurna dalam tasawuf Abdul karim al-Jilli yakni bidayah, tawasut dan khitam. Kajian ini menemukan bahwa pelaku kebaikan (muhsin) menurut Al-Qur’an adalah orang-orang yang melakukan segala kewajibannya dengan sebaik-baiknya, membalas setiap keburukan dengan kebaikan dan membalas kebaikan dengan kebaikan yang lebih besar, mampu menahan amarahnya, pemaaf, senantiasa memohon ampunan Allah atas dosa-dosa dan perbuatannya yang melampaui batas. Tingkatan ini diwujudkan dalam pertama, Perbuatan Ihsan Tingkatan Al-Bidayah (Tingkatan Permulaan) yakni karakter totalitas dalam berbuat kebajikan, dan karakter pemaaf; kedua, Tingkatan Al-Tawassuth (Tingkatan Pertengahan) pada Karakter empati sosial dan regulasi emosi; ketiga, Tingkatan Al-Khitam (Tingkatan Terakhir) dalam karakter respon positif, takwa dan tawadhu’